Estimating technical efficiency and bootstrapping Malmquist indices : analysis of Malaysian Preschool sector - Salleh Mad Ithnin, Habidin Nurul Fadly, Masnan Abdul Halim, Mamat Nordin, (Universiti Pendidikan Sultan Idris, 2016)
Estimating technical efficiency and bootstrapping Malmquist indices : analysis of Malaysian Preschool sector by Salleh Mad Ithnin, Habidin Nurul Fadly, Masnan Abdul Halim, Mamat Nordin,